2010
DOI: 10.1530/rep-09-0243
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the murine dynein light chain gene Tcte3-3 results in asthenozoospermia

Abstract: To elucidate the role of the mouse gene Tcte3 (Tctex2), which encodes a putative light chain of the outer dynein arm of cilia and sperm flagella, we have inactivated this gene in mice using targeted disruption. Breeding of heterozygous males and females resulted in normal litter size; however, we were not able to detect homozygous Tcte3-deficent mice using standard genotype techniques. In fact, our results indicate the presence of at least three highly similar copies of the Tcte3 gene (Tcte3-1, Tcte3-2, and Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…S2). Taken together, it is evident through restriction mapping that homologous recombination occurred in Tcte3-3 (Rashid et al, 2010).…”
Section: Increased Amount Of Tcte3 Modulates the Expression Patterns mentioning
confidence: 85%
See 4 more Smart Citations
“…S2). Taken together, it is evident through restriction mapping that homologous recombination occurred in Tcte3-3 (Rashid et al, 2010).…”
Section: Increased Amount Of Tcte3 Modulates the Expression Patterns mentioning
confidence: 85%
“…Although Tcte3 is predominantly expressed in testis, its expression had also been monitored in several other tissues lacking cilia or flagella (DiBella et al, 2001;Neesen et al, 2002). Previously, we reported that at least three copies of Tcte3 exist in mouse genome and subsequent inactivation of Tcte3-3 copy results in sperm motility defects thereby resulting in partial male infertility phenotype (Rashid et al, 2010). Evidently, Tcte3-3 À/À testis exhibited an increased rate of apoptosis in spermiogenesis.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations